The elastic rigidities of ribbed plates - Little, Robert Dryden (Department of Civil Engineering, 2016)
This thesis deals with the flexural and twisting rigidities of orthotropic plates. Asymmetrically stiffened plates are examples of technically orthotropic plates and are found in civil engineering structures such as bridges and ribbed floor slabs. The formulae for the rigidities as found in the literature are reviewed. The writer has devised an experimental method of determining the rigidities. This involves a bending test using the Moire technique and a twisting test. In the writer's method only one model is needed to determine all the rigidities. This is compared to other methods for which two or three models are needed. Sixteen different models of asymmetrically stiffened plates with ribs running in one direction only were made. The flexural rigidities of eight of these models and the twisting rigidities of all sixteen models were determined. The objective of the tests was to compare the test values with the theoretical values. More specifically the objective can be defined as follows. a) To determine how well an asymmetrically stiffened plate behaves as an orthotropic plate, i.e. how far apart may the ribs be spaced before the plate becomes a system of plate elements and beam elements. b) To determine the influence, if any, on the rigidities Dx, D₁ and Dy of altering the spacing of the ribs of stiffened plates which have the same theoretical values of Dx. c) To determine whether there is any difference between the rigidities D₁₂ and D₂₁, which are the same for a true orthotropic plate and are usually assumed to be the same for an asymmetrically stiffened plate. Conclusions are drawn on these points.